ANALYSIS OF STUDENT ACTIVITIES ON COMPUTER - A STUDY ON PUNJAB UNIVERSITY, INDIA - Suri, Dr Gunmala; Sharma, Sneha (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The purpose of this research is to investigate and understand how students are using computer. The activities that a student undertakes with the help of computers which might be fulfilling some academic or non academic purpose, is of great interest. It will help in understanding the limitations and potentials offered by the technology for use of computer in classroom. This paper brings out the three major kinds of activities that students undertake with computer; self learning activities, Information collection tasks and communication and group activities. The study further analyses the effect of demographics i.e. gender, age and faculty (department) of students on the activities with computer. The results show that gender has no impact on the activities of students with computer. The age impacts only the activities related to Information collection by using computer where as the faculty of student significantly impacts all the activities viz. self learning activities, Information collection tasks and communication and group activities. The findings from this research can be used in designing future e-learning initiatives and development e-learning tools